2023
DOI: 10.1007/s12672-023-00811-2
|View full text |Cite
|
Sign up to set email alerts
|

Association between testosterone and cancers risk in women: a two-sample Mendelian randomization study

Zhizhou Li,
Maoyu Wang,
Meimian Hua
et al.

Abstract: Objective Previous observational studies have explored the correlation between testosterone and cancer risk. However, the causal association between testosterone and various cancer types in women remains inconclusive. The objective of this Mendelian randomization study is to evaluate the causal links between total testosterone (TT) and bioavailable testosterone (BT) with cancer risk in females. Methods Initially, a rigorous quality control process … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…40 Furthermore, Li et al demonstrated a positive relation between total testosterone and bioavailable testosterone with BC risk (OR 1.17; 95% CI 1.08 to 1.27 and 1.14; 95% CI 1.06 to 1.22, respectively). 41 Another Mendelian randomisation was conducted to investigate the impact of testosterone and SHBG over cancer risk: total testosterone concentration was associated with BC in women (OR 1.14;…”
Section: Review Open Accessmentioning
confidence: 99%
“…40 Furthermore, Li et al demonstrated a positive relation between total testosterone and bioavailable testosterone with BC risk (OR 1.17; 95% CI 1.08 to 1.27 and 1.14; 95% CI 1.06 to 1.22, respectively). 41 Another Mendelian randomisation was conducted to investigate the impact of testosterone and SHBG over cancer risk: total testosterone concentration was associated with BC in women (OR 1.14;…”
Section: Review Open Accessmentioning
confidence: 99%